Working memory‐related changes in functional connectivity persist beyond task disengagement. Issue 3 (26th December 2012) - Gordon, Evan M.; Breeden, Andrew L.; Bean, Stephanie E.; Vaidya, Chandan J.
<x xml:space="preserve">Abstract</x> We examined whether altered connectivity in functional networks during working memory performance persists following conclusion of that performance, into a subsequent resting state. We conducted functional magnetic resonance imaging (fMRI) in 50 young adults during an initial resting state, followed by an N‐back working memory task and a subsequent resting state, in order to examine changes in functional connectivity within and between the default‐mode network (DMN) and the task‐positive network (TPN) across the three states. We found that alterations in connectivity observed during the N‐back task persisted into the subsequent resting state within the TPN and between the DMN and TPN, but not within the DMN. Further, both speed of working memory performance and TPN connectivity strength during the N‐back task predicted connectivity strength in the subsequent resting state. Finally, DMN connectivity measured before and during the N‐back task predicted individual differences in self‐reported inattentiveness, but this association was not found during the post‐task resting state. Together, these findings have important implications for models of how the brain recovers following effortful cognition, as well as for experimental designs using resting and task scans. Hum Brain Mapp 35:1004–1017, 2014. © 2012 Wiley Periodicals, Inc.